Anthropogenic Contaminants and Histopathological Findings in Stranded Cetaceans in the Southeastern United States, 2012–2018 - Page-Karjian, Annie; Lo, Catherine F.; Ritchie, Branson; Harms, Craig A.; Rotstein, David S.; Han, Sushan; Hassan, Sayed M.; Lehner, Andreas F.; Buchweitz, John P.; Thayer, Victoria G.; Sullivan, Jill M.; Christiansen, Emily F.; et al. (Frontiers in Marine Science, 2020)
Anthropogenic contaminants in the marine environment often biodegrade slowly, bioaccumulate in organisms, and can have deleterious effects on wildlife immunity, health, reproduction, and development. In this study, we evaluated tissue toxicant concentrations and pathology data from 83 odontocetes that stranded in the southeastern United States during 2012–2018. Mass spectrometry was used to analyze blubber samples for five organic toxicants (atrazine, bisphenol-A, diethyl phthalates, nonylphenol monoethoxylate [NPE], triclosan), and liver samples were analyzed for five non-essential elements (arsenic, cadmium, lead, mercury, thallium), six essential elements (cobalt, copper, manganese, iron, selenium, zinc) and one toxicant mixture class (Aroclor1268). Resultant data considerably improve upon the existing knowledge base regarding toxicant concentrations in stranded odontocetes. Toxicant and element concentrations varied based on animal demographic factors including species, sex, age, and location. Samples from bottlenose dolphins had significantly higher average concentrations of lead, manganese, mercury, selenium, thallium, and zinc, and lower average concentrations of NPE, arsenic, cadmium, cobalt, and iron than samples from pygmy sperm whales. In adult female bottlenose dolphins, average arsenic concentrations were significantly higher and iron concentrations were significantly lower than in adult males. Adult bottlenose dolphins had significantly higher average concentrations of lead, mercury, and selenium, and significantly lower average manganese concentrations compared to juveniles. Dolphins that stranded in Florida had significantly higher average concentrations of lead, mercury, and selenium, and lower concentrations of iron than dolphins that stranded in North Carolina. Histopathological data are presented for 72 animals, including microscopic evidence of Campula spp. and Sarcocystis spp. infections, and results of Morbillivirus and Brucella spp. molecular diagnostic testing. Sublethal cellular changes related to toxicant exposure in free-ranging odontocetes may lead to health declines and, in combination with other factors, may contribute to stranding.